A single LC tank based active voltage balancing circuit for battery management system - Habib, A K M Ahasan; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Alam, A. H. M. Zahirul (Kulliyah of Engineering, International Islamic University Malaysia (IIUM), 2018)
Nowadays, battery operated vehicles and machine power tools are becoming popular due to their simple and compact structure, low operating and maintenance costs, moreover renewable energy utilization facility etc. In order to obtain the necessary operating voltage and current of these devices, many electric cells are combined together in series and parallel combination. A series battery balancing circuit can be used to improve the efficiency of each cell charging and discharging process and consequently increase the lifespan of it. A battery management system (BMS) needs an efficient balancing circuit. This paper presents a high-speed single LC-tank DC to DC converter based electric cell balancing schemes. Since the supercapacitors are equivalent of rechargeable battery; in this research two supercapacitors have been used instead of rechargeable batteries. The voltage balance has been maintained by charging and discharging the supercapacitors through a single LC-tank circuit. As a result, the overall voltage balancing time has been reduced and improved the circuit performance. Experimental result shows that the proposed balancing circuit can reduce the voltage difference between the two supercapacitors from 350 mV to 0 V in 284 seconds, which is less time than the existing system.